2023
DOI: 10.1002/mnfr.202200620
|View full text |Cite
|
Sign up to set email alerts
|

Using a Metabotype Framework to Deliver Personalized Nutrition Improves Dietary Quality and Metabolic Health Parameters: A 12‐Week Randomized Controlled Trial

Abstract: Scope Effective strategies for tailoring dietary advice to individuals are urgently needed. The effectiveness of personalized nutrition advice delivered using a metabotype framework in improving dietary quality and metabolic health biomarkers compared to population‐level advice is investigated. Materials and results A 12‐week parallel randomized controlled trial is performed with 107 healthy adults. Individuals in the personalized group are classified into metabotypes using four markers (triacylglycerol, high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Our report contributes to an emerging trend of precision nutrition, using physiological measures to predict response to diet. Others have used postprandial glucose levels [ 6 ], k-means groups based on plasma triacylglycerol, total cholesterol, HDL-cholesterol, and glucose [ 41 ], and response to meal challenges (rev in [ 13 ]) to predict responses to dietary changes. The microbiome is also likely to contribute to individual responses to nutrition (rev.…”
Section: Primary Results [ 21 ]mentioning
confidence: 99%
See 1 more Smart Citation
“…Our report contributes to an emerging trend of precision nutrition, using physiological measures to predict response to diet. Others have used postprandial glucose levels [ 6 ], k-means groups based on plasma triacylglycerol, total cholesterol, HDL-cholesterol, and glucose [ 41 ], and response to meal challenges (rev in [ 13 ]) to predict responses to dietary changes. The microbiome is also likely to contribute to individual responses to nutrition (rev.…”
Section: Primary Results [ 21 ]mentioning
confidence: 99%
“…Virtually all plasma metabolites measured in the studies reviewed here were similar to the pattern observed for LDL-cholesterol ( Figure 2 ); that is, there was a “continuous” distribution of the measured metabolite across the population. As a step toward personalized nutrition, we and others are defining “metabolic groups”—or metabotypes [ 95 ] (and rev in [ 79 ])—as based on some a priori criteria [ 41 ] or through discovery-based approaches using unsupervised algorithms. Metabotypes group individuals with similar metabolic, genomic, or proteomic similarities.…”
Section: Secondary Resultsmentioning
confidence: 99%
“…The present paper reports secondary analyses carried out on data from participants that received personalised nutrition advice using a metabotype framework as part of a 12-week single-blind parallel RCT (ISRCTN15305840) ( 22 ). Throughout the study, participants attended three visits (baseline, week 4, and week 12) and received reports with dietary advice following baseline and week 4 visits.…”
Section: Methodsmentioning
confidence: 99%
“…Participants received personalised nutrition advice based on a metabotype framework previously published ( 23 , 24 ). The advice consisted of two reports containing three dietary goals each that were delivered following baseline and week 4 visits ( 22 ). Following week 4, participants were asked to follow both reports at the same time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation